Conservation : RIBA plan of work 2013 guide - Feilden, Hugh (The RIBA plan of work 2013 guide, 2017)
'Conservation' is part of a brand new series providing must-read practical guidance to running efficient and successful projects using the new RIBA Plan of Work 2013. Each guide takes a particular angle - in this case the author guides you through working on a conservation project - and explains the essential activities required at each stage.